Epidemiological and Clinical Aspects of Blinding Diseases in The National Teaching Hospital (Cnhu-Hkm) in Cotonou - ALAMOU, SOULÉ; Yehouessi, Lisette; Bra'Eyatcha Bymingo, Noelle; Sounouvou, Ignace; Tchabi, SIDONIE ELISE DJIDJOHO; DOUTETIEN, CLAUDIA (My University, 2016)
Objective: To study the epidemiological and clinical aspects of blinding diseases. Method: The study was retrospective, descriptive and analytical. It involved all patients with blindness and / or severe visual impairment and who came to consult in the Unit of Ophthalmology of the National Teaching Hospital from 1st March 2011 to 28 February 2013. Results: Among the 814 patients selected, 569 were suffering from blindness (69%) and 245 of severe visual loss (31%). The most affected were aged 50-59 years and 60-69 years with 247 cases for blindness (38.14%) and 124 cases for severe visual loss (50.21%). The sex ratio was 1.32. Retirees were the largest group of about 360; 44.22%. The other group with secondary education were the most numerous (36.61%). 102 and 114 patients respectively 17% and 19% had a history of glaucoma and cataracts. 33 patients had family history of glaucoma (4.05%) and 30 patients with a family history of blindness (3.69%). Ocular involvement was bilateral in 550 patients (67.57%). The crystalline (39.82%) and the optic nerve (17.78%) were the main anatomical sites of lesions found. Conclusion: To reduce the incidence of blindness and severe visual handicaps, it is important to study and improve the treatment of eye diseases.
Keywords: Blindness; Severe visual impairment; Visual impairment; Cataracts; Glaucoma